Evolution Model of Seepage Characteristics in the Process of Water Inrush in Faults - Jianli Shao; Fei Zhou; Wenbin Sun (Geofluids)
Although the mechanism and influence of fault water inrush have been widely studied, there are still few studies on the migration of filling particles and the evolution process of seepage characteristics within faults. In this work, the coupling effects of water flow, particle migration, and permeability evolution are considered synthetically, and the evolution model of seepage characteristics with multifield coupling is established. This model was used to investigate the evolution process of water inrush within faults and the effects of water pressure, initial effective porosity, and initial permeability on water flow rate. The results show that the evolution of seepage characteristics can be divided into three phases: (i) low velocity seepage, (ii) drastic changes with substantial particle migration, and (iii) steady-state water flow. The multifield coupling causes the effective porosity, permeability, flow velocity, and particle concentration to accelerate each other during the dramatic phase. Moreover, the increases in initial water pressure, initial porosity, and initial permeability have different degrees of promotion on the water flow rate. Finally, the simulation results are approximately the same as the data of water inrush in the mining area, which verifies the correctness of the evolution model established in this work. This work provides new approaches to the evolution process and prevention of water inrush in faults.